Study of dielectric behavior in PVDF/clay nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (E-Polymers, 2009)
A high dielectric permittivity nanocomposite based on poly( vinylidene fluoride) (PVDF) and organically modified clay is reported. The present work aims to study the effect of clay on dielectric behavior of PVDF. The dielectric permittivity study shows a remarkable enhancement in the permittivity of nanocomposites in the low frequency region. The obtained permittivity values fits quite well to the prediction of dielectric permittivity from Vo-Shi model, which takes contribution of interface to permittivity into account. This enhanced permittivity in nanocomposites is attributed to the presence of interfacial polarization. The interface effect is further studied with cole-cole plot analysis. The dielectric loss study of pristine PVDF shows two relaxations associated with segmental (glass transition relaxation) and crystalline chain relaxation. However in the PVDF/Clay nanocomposites crystalline relaxation peak disappears which is attributed to the formation of the beta phase in PVDF/clay nanocomposites.

Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy